A Conspectus of Management Control Theory: 1900-1972 - Giglioni, Giovanni B.; Bedeian, Arthur G. (Academy of Management Journal, 1974)
A comprehensive review of the literature on control theory, this paper examines the state of the art and provides a basis for rejecting the view that the executive can find very little knowledge to assist him in performing the control function.